Sulfur removal from crude oil using supercritical water. (2nd April 2016) - Demirbas, Ayhan
ABSTRACT: Desulfurization of crude oil using supercritical water (SCW) is one of the promising nonconventional processes for upgrading oil. SCW is an excellent solvent for high molecular weight organic compounds in crude oils. Low sulfur content of crude oil is particularly preferred. Water is one of the most commonly used supercritical fluids suitable as a substitute for organic solvents in a range of industrial processes. Supercritical fluid treatment depends on various parameters such as pressure, temperature, extraction time, solvent type, and chemical composition of the extracted material. SCW desulfurization has potential as a technique for removing sulfur from feedstocks such as heavy oil and bitumen. SCW upgrading of crude oils reduces sulfur content and decreases average molecular weight. Catalytic desulfurization of residual oil has been carried out through partial oxidation in supercritical water and thus 60% of the sulfur was removed.